2003
DOI: 10.1108/09600030310478810
|View full text |Cite
|
Sign up to set email alerts
|

Fourth generation ports – a question of agility?

Abstract: Since the Second World War, ports have been going through an evolution which the United Nations Conference on Trade and Development (UNCTAD) refers to as generations. The generation of a port reflects whether the approach adopted by port authorities/operators in developing their activities is likely to be reactive or proactive. These activities start with the traditional ones (cargo loading and discharging) and end up with the establishment of a wide range of logistics and value-added activities, developed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
175
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(188 citation statements)
references
References 17 publications
2
175
0
11
Order By: Relevance
“…For instance, Bichou and Gray (2005) propose that the performance of ports could be measured according to its contribution to overall added value of the channel. While some studies (i.e: Marlow and Paixao, 2003;Paixao and Marlow, 2003) offer logistics concepts such as leanness and agility for investigating port performance, other follow an empirical approach and suggest several constructs such as value-added services (i.e: Tongzon et al 2009) and information and communication systems (i.e: Panayides and Song, 2009). For instance, Carbone and De Martino (2003) investigate the contribution of a port to value creation through a case analysis, whereas Song and Panayides (2008) use 'use of information and communication technology', 'relationship with shipping line', 'value added service', 'integration of transport modes', and 'relationship with inland transport operators' as measures of port supply chain integration through a questionnaire survey.…”
Section: The Changing Role Of Ports and Integration Of Ports To Supplmentioning
confidence: 99%
“…For instance, Bichou and Gray (2005) propose that the performance of ports could be measured according to its contribution to overall added value of the channel. While some studies (i.e: Marlow and Paixao, 2003;Paixao and Marlow, 2003) offer logistics concepts such as leanness and agility for investigating port performance, other follow an empirical approach and suggest several constructs such as value-added services (i.e: Tongzon et al 2009) and information and communication systems (i.e: Panayides and Song, 2009). For instance, Carbone and De Martino (2003) investigate the contribution of a port to value creation through a case analysis, whereas Song and Panayides (2008) use 'use of information and communication technology', 'relationship with shipping line', 'value added service', 'integration of transport modes', and 'relationship with inland transport operators' as measures of port supply chain integration through a questionnaire survey.…”
Section: The Changing Role Of Ports and Integration Of Ports To Supplmentioning
confidence: 99%
“…The smaller ports can however look at their internal operations to find improvement opportunities. Paixao et al [9] builds a port development framework, based the United Nations Conference on Trade and Development's (UNCTAD's) "Port generations model". More details on UNCTAD can be found in Beresford et al [4].…”
Section: Optimising Terminal Operationsmentioning
confidence: 99%
“…Vertical integration strategies would help to extend the terminal operators' control over the chain, thus making them more attractive to be the chosen operator (De Souza et al, 2003). Paixao and Marlow (2003) claimed that ports have indeed become more integrated in supply chains. They introduced the logistics concepts of 'lean' and 'agile' operations as key indicators of port performance in supply chains, and suggested that a port's performance and competitiveness increasingly depend on logistics attributes in determining cost and responsiveness.…”
Section: Literature Reviewmentioning
confidence: 99%